Effect of Process Parameters on Formability of a AZ31 Magnesium Alloy Thin-Walled Cylindrical Part Formed by Multistage Warm Single-Point Incremental Forming - An, Zhi-guo; Yan, Dong; Qie, Jian-jian; Lu, Zai-liang; Gao, Zheng-yuan (Frontiers in Materials, 2020)
Magnesium alloys have many distinguished advantages, therefore, they are more and more popularly used in lightweight design of automotive and aviation manufacturing industry. However, its poor plasticity at room temperature has prevented its further application, especially in magnesium alloy sheets forming process. To expand the application of magnesium alloy sheets, single point incremental forming process for rapid prototype manufacturing and small scale productions of sheet metal was investigated. Combining finite element numerical simulations with physical experiments, the relationships between the maximum thickness differences and different process parameters are explored and the optimal process parameters for forming a certain straight wall cylindrical part of AZ31 magnesium alloy were determined. Based on the analysis of the results, the formability of AZ31 magnesium alloy sheet using warm SPIF is improved with the increases of number of forming stage, forming temperature and tool diameter but reduced with the increase of feed rate and interlayer spacing. The suitable forming temperature for AZ31 magnesium alloy sheet is about 250℃. For forming the deeper straight wall cylindrical parts, at least four forming stages are needed.